ANALISIS SUBSIDI ANGKUTAN PERDESAAN MELALUI BIAYA OPERASI KENDARAAN (BOK) DI KABUPATEN SLEMAN - . Marjanto (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2017)
Transport services rural areas in Sleman indicate operating performance is less well in service of nine routes. There are seven trajectories do not undergo trajectory corresponding permissions are set and one route is no longer operational.There is only one route which is still running track trajectory corresponding route permit.The purpose of this study was to analyze the performance of services of nine transportation route rural areas serving the route in Sleman District currently includes analysis : route network, load factor, headway, mileage, travel time, number of passengers and the speed of the average, the actual, the waiting location of transport and analyzing the financing scheme or calculate the amount of subsidy that can be applied to integrated rural transport to urban public transport serving in Sleman. Calculation of vehicle operating costs a small bus with a full subsidy for Rp.24,406,244,917/year, the difference in operating costs subsidy of Rp.18,318,644,917/year, bus subsidy grant of Rp. 18,559,117,225/year and fuel subsidies amounted Rp. .21,105,013,047. Recommended subsidy financing scheme because it is quite logical to be implemented is a subsidy mechanism for the difference in operating costs to buy the service system with the option of using a small bus.